BUILDING HISTORICAL AND CULTURAL AWARENESS THROUGH SOCIAL STUDIES LEARNING BASED ON CULTURAL EXHIBITION PROJECTS - Widyanti, Triani; Rohman, Slamet (Journal Civics And Social Studies, 2024)
Abstract The aim of this study is to enhance the historical and cultural awareness of students in the Social Studies Education program by creatively incorporating local wisdom values through a cultural exhibition project. The research method used was descriptive qualitative, which involved observation, interviews, and documentation of Social Studies Education students at IPI Garut. The findings of this study suggest that implementing social studies learning through cultural exhibition projects has enabled students to gain a more concrete understanding and knowledge, resulting in a more meaningful learning experience. This significance was evident in the students' increased awareness of the significance of understanding the history and culture of diverse ethnic groups in Indonesia, as well as the local wisdom values that contribute to the nation's prosperity and diversity. Furthermore, the process of creating various works for the cultural exhibition project has enabled students to develop new abilities and has inspired them to create more creative social studies learning media. It is hoped that these skills will be beneficial when the students enter the education field, both during their teaching practice and in their future careers as educators. Key words : Historical Awareness, Cultural Awareness, Social Studies Learning, Cultural Exhibition Project